PERAN GURU DALAM MENGATASI KENAKALAN SISWA SDN 83 PEKANBARU - Famela Ayuni; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Student delinquency is the behavior or actions of students that can cause problems, harm themselves or others, and violate moral values and social values. This study aims to determine (1) the teacher's role in dealing with student delinquency at SDN 83 Pekanbaru. This type of research is descriptive qualitative research. This research was conducted at SDN 83 Pekanbaru. The object of this research is student delinquency. The data collected are interview transcripts, observation sheets, and documentation. The data analysis technique uses the Miles and Huberman models, namely data collection, data presentation, data reduction, and drawing conclusions. Checking the validity of the data was carried out using the source triangulation technique. The results showed that (1) the forms of delinquency carried out by students were bullying, fighting and smoking. The role of the teacher in dealing with existing delinquency, namely the teacher's role in educating, training, guiding and dealing with student delinquency is (a) giving reprimands and advice, (b) giving punishment, and (c) making a student agreement. This effort was made to provide a deterrent effect so that he would not repeat his mischief again. Preventing student behavior in the form of delinquency requires an evaluation of school programs as well as collaborative efforts between the school and family.